2010
DOI: 10.4103/0972-2327.74197
|View full text |Cite
|
Sign up to set email alerts
|

Utility of molecular and serodiagnostic tools in cerebral toxoplasmosis with and without tuberculous meningitis in AIDS patients: A study from South India

Abstract: Background:Antemortem diagnosis of cerebral toxoplasmosis, the second most common opportunistic infection (OI) in HIV-infected individuals in developing countries is a challenge.Materials and Methods:Toxoplasma gondii (T.gondii) -specific serology and nested polymerase chain reaction (nPCR) were evaluated in sera and ventricular/lumbar cerebrospinal fluid (CSF) of 22 autopsy confirmed cases of cerebral toxoplasmosis with HIV and 17 controls. Frequency of concomitant T.gondii infection was investigated in 17 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
2
8
0
Order By: Relevance
“…In an earlier study from our Centre, we found serological tests for toxoplasmosis to be valuable for diagnosis especially when lumbar puncture is contraindicated as a diagnostic procedure [23]. …”
Section: Discussionmentioning
confidence: 99%
“…In an earlier study from our Centre, we found serological tests for toxoplasmosis to be valuable for diagnosis especially when lumbar puncture is contraindicated as a diagnostic procedure [23]. …”
Section: Discussionmentioning
confidence: 99%
“… The negative controls were from cases of road traffic accident (RTA) victims who were tested for toxoplasmosis. [ 2 ] These cases on testing were found to be negative for toxoplasmosis—it was not a deliberate selection. The cerebrospinal fluid samples from RTA cases are not collected at autopsy as the sample is usually contaminated with blood and will not be an ideal sample, to test.…”
mentioning
confidence: 99%
“…The serum IgG titers in the patients of group I (cases of confirmed central nervous system [CNS] toxoplasmosis) ranged from 196 to 1016 IU/mL [Table 2]. [ 2 ] We do agree that the mean serum IgG titers in our study were very high (646 IU/mL) since they were all terminally ill cases; however, a serum IgG titer of >200 IU/mL is considered positive in recrudescence cases indicating active disease and is useful in the antemortem diagnosis of CNS toxoplasmosis. [ 4 ] Our findings are in agreement with this observation indicated in literature.…”
mentioning
confidence: 99%
See 2 more Smart Citations